The role of human capital in the foreign market performance of US SMEs: does owner ethnicity matter?. Issue 7 (29th April 2021) - Ardito, Lorenzo; D'Angelo, Viviana; Petruzzelli, Antonio Messeni; Peruffo, Enzo
Abstract : Purpose: This paper adopts an intellectual capital perspective to investigate the role of owners who are ethnic minorities in the foreign market expansion performance of SMEs, and in particular considers the human capital dimension of intellectual capital. Design/methodology/approach: Based on the empirical investigation of a sample of 10, 326 small- and medium-sized US high-tech manufacturing enterprises, the authors' results reveal a positive relationship between the number of foreign markets where these SMEs operate and their financial performance, and that this effect is reinforced by the presence of ethnic minority owners, as ethnic minorities constitute a valuable source of intellectual capital which bring value to firms. Findings: The authors' findings reveal the importance of intellectual capital in an SME's leadership position, specifically in terms of having individuals from normally disadvantaged groups as owners. In this sense, policymakers are crucial in supporting the inclusion of ethnic minorities in SME ownership, through advantageous treatment in firms, for example. Practical implications: The study presents practical implications for managers seeking foreign market expansion. In addition, when defining ownership structure (e.g., in the start-up phase), the role of human capital, in the form of ethnic minorities, should not be neglected, especially if an SME intends to operate or is already operating in different national contexts. Originality/value: The authors' results provide important insights into the positive effect of human capital on SME foreign market performance. The idea of a moderating role played by owners from ethnic minorities suggested here contributes to the literature on human capital and is one of the first attempts to consider this moderating factor in this relationship, especially in the SME context.